2013
DOI: 10.1021/cm401849f
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Bonding Complexes Based on Bis(iodoethynyl)benzene Units: A New Versatile Route to Supramolecular Materials

Abstract: Iodoalkynes [1,benzene (p-BIB) and 1,3-bis(iodoethynyl)benzene (m-BIB)] have been used successfully to prepare halogen bonding complexes with a range of 4-pyridine derivatives showing liquid crystalline organizations. The trimeric halogen-bonded complexes obtained from p-BIB have a rod-like structure and exhibited high order calamitic phases (SmB and G). In contrast, m-BIB gives rise to bent-shaped structures that display SmAP-like mesophases. Furthermore it was found that the presence of three and five aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 57 publications
1
67
0
Order By: Relevance
“…The field has expanded over the years, as has also been reviewed recently [50]. The majority of halogen-bonded LCs are assembled by combining alkoxystilbazoles, widely used promesogenic molecules [51], with halogen-bond donors such as iodoperfluorobenzenes [52], iodoperfluoroalkanes [53], iodoacetylenes [54], and molecular iodine [55]. From these examples, one could argue that very strong halogen-bond donors are required to stabilize the high-temperature mesophases, and that only molecules containing highly electrophilic iodine atoms are suitable for the task.…”
Section: Photoactive Halogen-bonded Liquid Crystalsmentioning
confidence: 99%
“…The field has expanded over the years, as has also been reviewed recently [50]. The majority of halogen-bonded LCs are assembled by combining alkoxystilbazoles, widely used promesogenic molecules [51], with halogen-bond donors such as iodoperfluorobenzenes [52], iodoperfluoroalkanes [53], iodoacetylenes [54], and molecular iodine [55]. From these examples, one could argue that very strong halogen-bond donors are required to stabilize the high-temperature mesophases, and that only molecules containing highly electrophilic iodine atoms are suitable for the task.…”
Section: Photoactive Halogen-bonded Liquid Crystalsmentioning
confidence: 99%
“…26 Alternatively, the intended XB donor can be connected to an sp-hybridized carbon atom which facilitates polarization and leads to an enhanced positive charge. 27,28,29 Only in very rare cases has a combination of approaches been deliberately utilized in order to create an activated XB donor. 30,31 In order to develop a new series of potent XB donors for effective co-crystal synthesis, we decided to combine the electron-withdrawing capabilities of -NO 2 moieties with the polarizing effects of an sp-carbon atom thereby providing a path to highly electrophilic halogen atoms through a 'double-activation' process, Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Gonzalez et al. reported on halogen‐bonded complexes using bis(iodoethynyl)benzene isomers and pyridine derivatives (Scheme ) . The linear trimeric halogen‐bonded complexes derived from 1,4‐bis(iodoethynyl)benzene show smectic B and crystal G mesophases (Figure ).…”
Section: Halogen‐bonded Liquid Crystalsmentioning
confidence: 99%
“…reportedo nh alogen-bonded complexes using bis(iodoethynyl)benzene isomers and pyridine derivatives (Scheme 10). [80] The linear trimeric halogen-bonded complexes derived from 1,4-bis(iodoethynyl)benzenes how smectic Ba nd crystal Gm esophases (Figure 7). The bent shaped complexes derived from 1,3-bis(iodoethynyl)benzenee xhibited SmAP-like liquid crystal phases, in whcih "P" stands for polar.I t was observed that the mesophase behaviors in thesec omplexes are dependent on the number of aromatic rings present.…”
Section: Scheme6chemical Structures Of Trimeric Halogen-bonded Complmentioning
confidence: 99%